Pengaruh Persepsi Kemudahan Penggunaan dan Kualitas Pelayanan terhadap Keputusan Konsumen menggunakan Fitur Shopee Food dalam Aplikasi Shopee (Studi Kasus pada Pengguna Fitur Shopee Food di Kota Bekasi) - Setyoadi, Mas Andrianto; Rusyda, Salma (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2023)
This study aims to determine the Influence of Perception on Convenience of Usage and Quality of Service toward Consumer Decisions on using Shopee Food Feature in Shopee Application. The research method used is a quantitative method. Data collection techniques used in the form of questionnaires and literature. The population of this study is the Shopee Food Feature Users in Bekasi City. The sampling technique in this study is non-probability sampling with population sampling method. Samples are 100 samples. The result showed that the Perception on Convenience of Usage had an influence on the decision to use features by 51.4%. Quality of Service has an effect of 58.9% of Decision to Use Features. Perception on Convenience of Usage and Quality of Service have a significant effect on the Decision of Feature Usage. Perception on Convenience of Usage and Quality of Service influence the Decision of Feature Usage simultaneously with a value of 0.638 or 63.8% of which 38.2% is explained by other factors not included in this study.